Overcoming GNA/RNA base-pairing limitations using isonucleotides improves the pharmacodynamic activity of ESC+ GalNAc-siRNAs. Issue 19 (14th October 2021) - Schlegel, Mark K; Matsuda, Shigeo; Brown, Christopher R; Harp, Joel M; Barry, Joseph D; Berman, Daniel; Castoreno, Adam; Schofield, Sally; Szeto, John; Manoharan, Muthiah; Charissé, Klaus; Egli, Martin; et al.
Abstract: We recently reported that RNAi-mediated off-target effects are important drivers of the hepatotoxicity observed for a subset of GalNAc–siRNA conjugates in rodents, and that these findings could be mitigated by seed-pairing destabilization using a single GNA nucleotide placed within the seed region of the guide strand. Here, we report further investigation of the unique and poorly understood GNA/RNA cross-pairing behavior to better inform GNA-containing siRNA design. A reexamination of published GNA homoduplex crystal structures, along with a novel structure containing a single ( S )-GNA-A residue in duplex RNA, indicated that GNA nucleotides universally adopt a rotated nucleobase orientation within all duplex contexts. Such an orientation strongly affects GNA-C and GNA-G but not GNA-A or GNA-T pairing in GNA/RNA heteroduplexes. Transposition of the hydrogen-bond donor/acceptor pairs using the novel ( S )-GNA-isocytidine and -isoguanosine nucleotides could rescue productive base-pairing with the complementary G or C ribonucleotides, respectively. GalNAc-siRNAs containing these GNA isonucleotides showed an improved in vitro activity, a similar improvement in off-target profile, and maintained in vivo activity and guide strand liver levels more consistent with the parent siRNAs than those modified with isomeric GNA-C or -G, thereby expanding our toolbox for the design of siRNAs with minimized off-target activity.